2019
DOI: 10.2174/1573402115666190119163942
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress, Adhesion Molecules and Antioxidants in Preeclampsia

Abstract: Oxidative stress is a consequence of reduction in the antioxidant capacity and excessive production of reactive oxygen and nitrogen species (ROS). Oxidative agents, which are overproduced due to ischemic-reperfusion injury in the placenta, may overwhelm the normal antioxidant activity. This imbalance is a key feature in the pathogenesis of preeclampsia. A decrease in glutathione peroxidase (GPX) activity is associated with the synthesis of vasoconstrictive eicosanoids such as F2-isoprostanes and thromboxane, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…MDA is a major metabolite of lipid peroxide breakdown and one of the first biomarkers of oxidative stress found in the maternal circulation of women with PE (Myatt and Cui, 2004;Kaur et al, 2008;Poston et al, 2011;Haram et al, 2019). Thus, the similarities of findings in hypertensive animal models, such as those used in the present study, with those described in pregnant women (Myatt and Cui, 2004;Kaur et al, 2008;Poston et al, 2011) support the use of these animal models in translational pregnancy research.…”
Section: Discussionsupporting
confidence: 67%
“…MDA is a major metabolite of lipid peroxide breakdown and one of the first biomarkers of oxidative stress found in the maternal circulation of women with PE (Myatt and Cui, 2004;Kaur et al, 2008;Poston et al, 2011;Haram et al, 2019). Thus, the similarities of findings in hypertensive animal models, such as those used in the present study, with those described in pregnant women (Myatt and Cui, 2004;Kaur et al, 2008;Poston et al, 2011) support the use of these animal models in translational pregnancy research.…”
Section: Discussionsupporting
confidence: 67%
“…Oxidative stress is due to an excessive production of reactive oxygen and nitrogen species (Ilekis et al, ) and a reduction in the antioxidant capacity. In the pathogenesis of PE, the balance between oxidants and antioxidants is broken, being one of the key features of PE (Haram, Mortensen, Myking, Magann, & Morrison, ). Ekun et al indicated lower SOD and higher MDA levels in PE women's blood samples, suggesting the association of PE with oxidative stress (Ekun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…ADM (adrenomedullin), whose expression/secretion is known to be reduced in STB from PE placentae 43 , was enriched 2.4-fold in control-over PE-iPSC derived STB. GPX3 and GPX4, members of the glutathione peroxidase family known to play crucial roles in defense against oxidative stress 16,44,45 , showed 3.6-fold and 1.5-fold higher expression, respectively, in STB derived from control-iPSC vs. PE-iPSC. Activating Transcription Factor 3 (ATF3), associated with both apoptosis and UV response gene sets, was enriched threefold in control-iPSC-derived STB.…”
Section: Global Gene Expression In Pe and Control Ipsc-derived Trophomentioning
confidence: 99%